Dysregulation of Rnf 213 gene contributes to T cell response via antigen uptake, processing, and presentation. Issue 11 (10th May 2021) - Tashiro, Ryosuke; Niizuma, Kuniyasu; Kasamatsu, Jun; Okuyama, Yuko; Rashad, Sherif; Kikuchi, Atsuo; Fujimura, Miki; Kure, Shigeo; Ishii, Naoto; Tominaga, Teiji
Abstract: Growing evidence suggest the association between Moyamoya disease (MMD) and immune systems, such as antigen presenting cells in particular. Rnf213 gene, a susceptibility gene for MMD, is highly expressed in immune tissues, however, its function remains unclear. In addition, the physiological role of RNF213 gene polymorphism c.14576G > A (rs112735431), susceptibility variant for MMD, is also poorly understood. By studying Rnf213 ‐knockout ( Rnf213 ‐KO) mice with deletion of largest exon32 and Rnf213 ‐knockin ( Rnf213 ‐KI) mice with insertion of single‐nucleotide polymorphism corresponding to c.14576G > A mutation in MMD patients, we aimed to investigate the role of RNF213 in dendritic cell development, and antigen processing and presentation. First, we found a high level of Rnf213 gene expression in conventional DCs and monocytes. Second, flow cytometric and confocal microscopic analysis revealed ovalbumin protein‐pulsed Rnf213 ‐KO and Rnf213 ‐KI DCs showed impaired antigen uptake, proteolysis and reduced numbers of endosomes and lysosomes, and thereby failed to activate and proliferate antigen‐specific T cells efficiently. In addition, Rnf213 ‐KI DCs showed a similar phenotype to that of Rnf213 ‐KO BMDCs. In conclusion, our findings suggest the critical role of RNF213 in antigen uptake, processing and presentation. Abstract : Rnf213 gene, susceptibility gene for moyamoya disease, is highly expressed in dendritic cells. Dysregulation of Rnf213 gene lead to impaired antigen uptake, processing and presentation, leading to impaired T cell response.